Development of Multiple Intelligence-Based Instructional Design - Villanueva, Danica P; De Vera, Gemma M (ASEAN Multidisciplinary Research Journal, 2020)
Several studies have found out that students vary immensely in terms of interest, skill and in intelligence that definitely contributed to their perspectives, participation and performance in academic matters. Students though differ from each other, certainly looking for activities and exciting tasks where they can learn the lesson and to where they can apply their intelligences. Allowing the students to choose and do task which interests them and at the same time they can mobilize their intelligences could surely increase their participation and performance especially to the genres of literature that they are low performing. Thus, this study focused on the development of instructional design that is multiple intelligence-based that could be used to teach the least mastered genres of literature. This study used the descriptive and developmental method of research. In identifying the multiple intelligences of the student-respondents, a survey questionnaire was administered to 214 Grade 9 students from the randomly selected sections of Alaminos City National High School, Alaminos City, Pangasinan. Findings showed that the student-respondents’ prevailing multiple intelligences are Visual-Spatial, Bodily-Kinesthetic and Verbal-Linguistic. They are also low performing in poem and short story genres of literature. The series of lesson plan as the developed instructional design is anchored to the prevailing intelligences of the students that could be used to help the student-respondents improve their learnings in their least mastered genres of literature.